\(a)\) Ta có :
\(A=\frac{6n-2}{3n+1}=\frac{6n+2-4}{3n+1}=\frac{2\left(3n+1\right)-4}{3n+1}=\frac{2\left(3n+1\right)}{3n+1}-\frac{4}{3n+1}=2+\frac{4}{3n+1}\)
Để A là số nguyên thì \(\frac{4}{3n+1}\) phải là số nguyên \(\Rightarrow\)\(4⋮\left(3n+1\right)\)\(\Rightarrow\)\(\left(3n+1\right)\inƯ\left(4\right)\)
Mà \(Ư\left(4\right)=\left\{1;-1;2;-2;4;-4\right\}\)
Do đó :
\(3n+1\) | \(1\) | \(-1\) | \(2\) | \(-2\) | \(4\) | \(-4\) |
\(n\) | \(0\) | \(\frac{-2}{3}\) | \(\frac{1}{3}\) | \(-1\) | \(1\) | \(\frac{-5}{3}\) |
Lại có \(n\inℤ\) nên \(n\in\left\{-1;0;1\right\}\)
Câu b) là tương tự rồi tính n ra, sau đó thấy n nào giống với câu a) rồi trả lời